The Effect of Job Satisfaction on Work Performance with Mediated Work Life Balance: English - Hanna Gricilia Tampubolon; Suryani Hardjo; Patisina (Ilomata International Journal of Social Science, 2026)
This study aims to examine the direct impact of job satisfaction on individual work performance, as well as the indirect influence mediated by work-life balance. The data were collected using instruments designed to assess job satisfaction and work-life balance, while work performance data were obtained from relevant institutions. The sample was obtained through convenience sampling, yielding a total of 78 employees. The findings of this study demonstrate both direct and indirect effects of job satisfaction on work performance, although the mediator work-life balance did not exert a greater effect than job satisfaction. This study contributes to the organizational and industrial context, demonstrating that job satisfaction is a key issue that needs improvement, rather than work-life balance, which is an external issue within the organizational and industrial context. Unlike previous research that demonstrated that work-life balance plays a significant role in one's work performance, this study demonstrates that job satisfaction is far more effective in improving work performance. Limitations and recommendations are explained further in this article.